Impact of the Recent Changes in the Pharmacy Remuneration System in Portugal (2010-2014) – Moving from Paper to Reality - I Teixeira; JP Teixeira; S Costa (Revista Portuguesa de Farmacoterapia, 2019)
Objective The pharmacies and wholesalers’ remuneration system for the provision of medicines in Portugal went under structural changes with the Memorandum of Understanding in 2011, which intensified the degree of public pharmaceutical expenditure reduction requirements, in exchange for the financial international assistance. The objectives of the present study were: to provide an overview of the changes, its impact for pharmacies and recent advances towards a more comprehensive system.